1991
DOI: 10.1128/aem.57.10.2928-2934.1991
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the antifungal activity of a soilborne Pseudomonas aureofaciens strain

Abstract: Pseudomonas aureofaciens Q2-87 produces the antibiotic 2,4-diacetophloroglucinol (Phl), which inhibits Gaeumannomyces graminis var. tritici and other fungi in vitro. Strain Q2-87 also provides biological control of take-all, a root disease of wheat caused by this fungus. To assess the role of Phl in the antifungal activity of strain Q2-87, a genetic analysis of antibiotic production was conducted. Two mutants of Q2-87 with altered antifungal activity were isolated by site-directed mutagenesis with TnS. One mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(72 citation statements)
references
References 27 publications
2
65
0
3
Order By: Relevance
“…DAPG has been well documented for its ability to suppress soil-borne fungal pathogens of root and seedling diseases. Some well-studied DAPG producing strains such as P. fluorescens CHAO, F113, Q2-87 and Q8r1-96 have been successfully used against black root rot of tobacco, crown and root rot of tomato, Pythium damping-off of cucumber and sugar beet, take-all of wheat and cyst nematode and soft rot of potato (Stutz et al 1986;Fenton et al 1992;Keel et al 1992;Vincent et al 1991;Harrison et al 1993;Cronin et al 1997;Duffy and Défago 1997;Raaijmakers and Weller 1998). Genetic studies demonstrate the role of DAPG in biological control, which is complemented by direct isolation of DAPG from the rhizosphere .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DAPG has been well documented for its ability to suppress soil-borne fungal pathogens of root and seedling diseases. Some well-studied DAPG producing strains such as P. fluorescens CHAO, F113, Q2-87 and Q8r1-96 have been successfully used against black root rot of tobacco, crown and root rot of tomato, Pythium damping-off of cucumber and sugar beet, take-all of wheat and cyst nematode and soft rot of potato (Stutz et al 1986;Fenton et al 1992;Keel et al 1992;Vincent et al 1991;Harrison et al 1993;Cronin et al 1997;Duffy and Défago 1997;Raaijmakers and Weller 1998). Genetic studies demonstrate the role of DAPG in biological control, which is complemented by direct isolation of DAPG from the rhizosphere .…”
Section: Discussionmentioning
confidence: 99%
“…The broad-spectrum antimicrobial activity of DAPG produced by fluorescent pseudomonads has drawn great attention to agriculture because of its ability to suppress plant pathogens and play a key role in the biological control (Keel et al 1996; Thomashow and Weller 1996;Duffy and Défago 1997;Duffy et al 2004). DAPG-producing strains such as P. fluorescens Pf5, CHA0, F113, Q2-87, Q8r1-96 (Howell and Stipanovic 1980;Vincent et al 1991;Harrison et al 1993;Pierson and Weller 1994;Cronin et al 1997;Raaijmakers and Weller 1998;Duffy and Défago 1999) have been used to suppress the black root rot of tobacco, root rot of tomato, Pythium damping-off of cucumber and sugar beet, cyst nematode and soft rot of potato and take-all of wheat. Although antagonistic fluorescent pseudomonads associated with banana have been studied earlier (Banerjee and Langhe 1985;Sutra et al 2000), the role of DAPG or DAPG-producing bacterium for the suppression of banana wilts and root necrosis pathogens have not been reported so far.…”
mentioning
confidence: 99%
“…In one such strain, designated CHA0, hydrogen cyanide (HCN) and 2,4-diacetylphloroglucinol (Phl; Keel et al, 1992) have been shown to be major determinants of the strain's biocontrol ability. HCN and, especially, Phl are also implicated in the biological control of soil-borne phytopathogens by other antagonistic fluorescent pseudomonads (Vincent et al, 1991;Fenton et al, 1992;Keel et al, 1992;Cronin et al, 1997;Ellis et al, 2000;Haas & Keel, 2003;Moënne-Loccoz & Défago, 2004). In addition, Phl 1 pseudomonads and Phl synthesis contribute to the monoculture decline of take-all disease of wheat caused by Gaeumannomyces graminis var.…”
Section: Introductionmentioning
confidence: 99%
“…Phl is a polyketide displaying antifungal as well as antibacterial, antiviral, antihelminthic, antinematode and phytotoxic properties in vitro [11^14]. The use of Phl-minus derivatives of Pseudomonas £uorescens CHA0, F113 and Q2-87 in soil microcosms has shown the importance of Phl in disease suppression by the corresponding wildtype strains [3,13,15,16]. Moreover, Phl has been detected in the rhizosphere of plants colonized by Phl strains CHA0 (under gnotobiotic conditions; [13]) and Q2-87 (in non-sterile soil; [17]).…”
Section: Introductionmentioning
confidence: 99%